2023
DOI: 10.3390/su16010128
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Small Mammals’ Body Condition in Eucalyptus Dominated Landscapes

Beatriz C. Afonso,
Gonçalo Matias,
Daniela Teixeira
et al.

Abstract: The timber industry has increased considerably in recent decades to meet human needs for wood. In Portugal, Eucalyptus plantations are the most common use of forested land, presenting the largest coverage of Eucalyptus globulus in Europe. Although it is established that this landscape can affect biodiversity patterns, it is not clear what its role in shaping small mammals’ body condition is. Here, we tested the effect of Eucalyptus plantations on small mammals’ body condition, together with vegetation structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…However, in the case of Tullberg’s soft-furred mouse ( Praomys tullbergi ), habitat influence was not pronounced [ 24 ]. Other studies in low latitudes have shown that habitat and habitat fragmentation affect the body condition of individuals [ 25 , 26 ]. Our current study will definitively fill the gap in BCI information from the middle latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of Tullberg’s soft-furred mouse ( Praomys tullbergi ), habitat influence was not pronounced [ 24 ]. Other studies in low latitudes have shown that habitat and habitat fragmentation affect the body condition of individuals [ 25 , 26 ]. Our current study will definitively fill the gap in BCI information from the middle latitudes.…”
Section: Introductionmentioning
confidence: 99%